DASAR MISI ALLAH DALAM KEJADIAN 1-11 - Traugott G. R Boeker (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2018)
This writing contains the basis of God’s revelation to man as it is found in Genesis 1-11. All Scriptures (66 books) are God’s word without exception. Critical studies are insufficient to applied to God’s word, for He is our Creator and Judge, to whom we all are in charge. By understanding God in the Old Testament according to His work of creation, we - then - come to conclusion that God’s mission to all people / nations is mostly needed. Man will surely die without God. God’s heart and mission are clearly seen in Genesis 1-11. The teachings revealed in these chapters are still relevant for the believers now. This writing is recommended to pastors to comprehend mission based on the bible and to teach them to the church goers.